Investigating How Instructional Practices Affect Reading and Writing Difficulties among Primary Level Students: A Case Study of Oxford Secondary School (OCEM Journal of Management, Technology & Social Sciences, 2026)
Early literacy development is fundamental to academic success, yet many primary-level students experience persistent difficulties in reading and writing. This case study examined the factors contributing to literacy challenges among students in Grades 1– 4 at Oxford Secondary School, with particular attention to the influence of traditional teacher-centered pedagogy on literacy skill development. The study aimed to identify specific barriers to reading and writing proficiency and evaluate instructional approaches that support struggling learners. A mixed-methods design was employed, integrating qualitative classroom observations and teacher interviews with quantitative analyses of student assessment data.The study investigated twenty-seven (N=27) students with reading and writing difficulties through video recordings and an individualised learning assessment project over two months. It uncovered a literacy–rote-learning paradox: students excelled at structured memorisation tasks but struggled with functional literacy, particularly in English sentence construction and Nepali phonics. Major challenges identified included underdeveloped motor skills affecting writing speed and legibility, a lack of a systematic writing process, and a teacher-centered instructional approach that favored theoretical knowledge over practical skills.The results showed that practice-based instructional strategies and individualised support led to a 33% improvement in literacy performance over six weeks. The study concludes that traditional student-centered methods alone are insufficient for supporting learners with literacy challenges unless coupled with structured interventions. Key findings highlight the importance of practice-oriented pedagogy, motor skill development, a four-stage writing process, and enhanced collaboration between parents and teachers to improve early literacy outcomes and maintain learning progress among primary-level students.